2022
DOI: 10.1021/acs.inorgchem.2c02150
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between β-Diimino and β-Diketiminato Ligands in Nickel Complexes Active in the Proton Reduction Reaction

Abstract: Two Ni complexes are reported with κ4-P2N2 β-diimino (BDI) ligands with the general formula [Ni­(XBDI)]­(BF4)2, where BDI is N-(2-(diphenylphosphaneyl)­ethyl)-4-((2-(diphenylphosphaneyl)­ethyl)­imino)­pent-2-en-2-amine and X indicates the substituent in the α-carbon intradiimine position, X = H for 1(BF4)2 and X = Ph for 2(BF4)2. Electrochemical analysis together with UV–vis and NMR spectroscopy in acetonitrile and dimethylformamide (DMF) indicates the conversion of the β-diimino complexes 12+ and 22+ to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(83 reference statements)
1
5
0
Order By: Relevance
“…Efforts to isolate catalytic intermediates, as well as to independently synthesize partially reduced nickel calixpyrrole complexes are currently underway. Furthermore, it should be noted that hydrogen evolution pathways that invoke a Ni III ‐hydride cannot be ruled out at this time [85–89] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to isolate catalytic intermediates, as well as to independently synthesize partially reduced nickel calixpyrrole complexes are currently underway. Furthermore, it should be noted that hydrogen evolution pathways that invoke a Ni III ‐hydride cannot be ruled out at this time [85–89] …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it should be noted that hydrogen evolution pathways that invoke a Ni III -hydride cannot be ruled out at this time. [85][86][87][88][89]…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
“…A wide range of overpotential values have been reported between 0.01 and 1.0 V, and our estimation fits well within these margins. [42][43][44][45] We took this estimated value of 0.540 V for overpotential, and applied it to the main experiment, which was carried out under galvanostatic conditions. We concluded that the applied potential had to be 0.820 V, and this produced a reaction yield of 89 %, which is very close to the experimental result which is 86 % isolated yield.…”
Section: Microkinetic Models and Overpotentialmentioning
confidence: 99%
“…Most recently, the conversion between β-Diimino and β-Diketiminato ligands ( 30 ) was reported for two Ni( ii ) N 2 P 2 complexes. 73 Upon reaction with Ni(BF 4 ) 2 ·6H 2 O, the β-Diketiminato ligand was converted to a square planar Ni( ii ) β-Diimino complex with two tetrafluoroborate anions. The Ni( ii ) β-Diketiminato complex can be accessed from the Ni( ii ) β-Diimino complex in the presence of a very weak base such as DMF due to the increased acidity of the α-CH proton upon metalation.…”
Section: Introductionmentioning
confidence: 99%